Publications on Women's Issues and Gender Concerns by UP Faculty, REPS & Students: An Annotated Bibliography - Ranosa, Rachel May (Review of Women's Studies; Vol 16 No 1-2 (2006): Review of Women's Studies Volume XVI, Numbers 1-2 (January-December 2006), 2023)
---